2000
DOI: 10.1097/00003246-200005000-00055
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward limitation of support in a pediatric intensive care unit

Abstract: When making decisions about whether or not to limit care for a patient, caregivers were more likely to rely on the perceived benefit to the patient than preadmission quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 13 publications
1
41
0
4
Order By: Relevance
“…By comparing the data obtained from studies on modes of death conducted at U.S. and Canadian hospitals, it is observed that the incidence of CPR prior to the death of patients at the three analyzed PICUs (53%) was extremely high. 6,10,15 One should recall that CPR is indicated in cases of unexpected cardiorespiratory arrest. A large number of infants who die at PICUs every day have chronic diseases and stand no chance to have their disease controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the data obtained from studies on modes of death conducted at U.S. and Canadian hospitals, it is observed that the incidence of CPR prior to the death of patients at the three analyzed PICUs (53%) was extremely high. 6,10,15 One should recall that CPR is indicated in cases of unexpected cardiorespiratory arrest. A large number of infants who die at PICUs every day have chronic diseases and stand no chance to have their disease controlled.…”
Section: Discussionmentioning
confidence: 99%
“…All the physicians who helped with the research received a previous training before the data collection, in which they had to read classic articles on modes of death in the ICU, followed by simulate cases for the classification of the modes of death and a theoretical lesson on the subject. 5,15 Two sessions were necessary so that the reliability of the data, assessed by kappa statistics, reached 0.9. Data collection only started after this value was reached.…”
Section: Methodsmentioning
confidence: 99%
“…11 The revelation about the presence of paralyzing agents in some patients at the time of withdrawal of LST and that 2% of the involved professionals believed that hastening death is an acceptable goal in itself generated great controversy. 12-14 Consequently, more information about pediatric intensivists' actual practices regarding forgoing LST in children 8,10,15,16 is warranted. Some details about these events, such as timing of decision making, terminal sedation, barriers to achieve consensus with families, and their participation in the process, remain topics that need additional exploration.…”
mentioning
confidence: 99%
“…Further, nurses were asked what type of end-of-life decision they considered the most important made. In nearly half of the end-of-life decisions (49%), a nontreatment decision www.ajcconline.org (89) 70 (50) 41 (29) 30 (21) 50 (35) 35 (25) 23 (16) 33 (23) 0 (0) 135 (96) 6 (4) NA NA NA NA NA NA NA NA NA NA NA 14 (16) 74 (84) 52 (58) 22 (25) 15 (17) 34 (38) 21 (24) 20 (22) 14 (16) 3 (3) 84 (94) 2 (2) 24 (27) 14 (16) 3 (3) 13 (15) 16 (18) 19 (21) 25 (28) 35 (39) 29 (33) 62 (70) 27 (30) Abbreviation: NA, not available. a Percentages may not total 100 because of rounding.…”
Section: Medical End-of-life Decisions In Picusmentioning
confidence: 99%
“…This result is also in keeping with previous findings. 28,32,33 Furthermore, nurses consider the involvement of parents in the decision to be important. 27 Apparently, PICU nurses comply with international guidelines that state that decisions should be jointly made by physicians and parents.…”
Section: Nurses' Attitudes Toward End-of-life Decisionsmentioning
confidence: 99%